2015
DOI: 10.1089/acm.2014.0021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hippotherapy on Gross Motor Function in Children with Cerebral Palsy: A Randomized Controlled Trial

Abstract: Hippotherapy positively affects gross motor function and balance in children with CP of various functional levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1
46

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 27 publications
4
54
1
46
Order By: Relevance
“…Previous research on the association between horseback riding and walking has shown that horseback riding improved the walking speed and distance of palsy patients (Kwon et al, 2015), and similar results were found in stroke patients who participated in hippotherapy .…”
Section: ⅳ Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Previous research on the association between horseback riding and walking has shown that horseback riding improved the walking speed and distance of palsy patients (Kwon et al, 2015), and similar results were found in stroke patients who participated in hippotherapy .…”
Section: ⅳ Discussionsupporting
confidence: 71%
“…Kwon (2015)'s study showed that horseback riding improved gross motor function in children with cerebral palsy, and Im and Huh (2013) study showed that hippotherapy led to a statistically significant improvement in gross motor function and balance in children with brain lesions. Champagne and Dugas (2010) also reported that hippotherapy enhanced stability, gross motor function, and control of the head and the trunk.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A melhora na função motora grossa em crianças com PC tem sido relatada em estudos anteriores utilizando a GMFM, e esta melhora está relacionada com o nível GMFCS da criança [16,17]. No presente estudo, os praticantes com PC apresentaram uma melhora significativa da função motora grossa de forma global após as sessões de equoterapia.…”
Section: Discussionunclassified
“…[33][34][35] Kwon JY, Chang HJ, Yi SH, Lee JY, Shin HY, Kim YH realizaron un ensayo clínico aleatorizado con 92 niños con diagnóstico de parálisis cerebral a quienes le evaluaron la función motora gruesa, la intervención consistió en 30 minutos de hipoterapia por 8 semanas consecutivas encontrando diferencias significativas para los diferentes niveles de motricidad gruesa y el balance. 38 b. Marcha humana La marcha humana es definida como una serie de movimientos alternantes, rítmicos de las extremidades y del tronco que resultan en un desplazamiento hacia adelante del centro de gravedad. 39 A través de electromiografía dinámica se ha podido comprobar que la mayoría de los grupos musculares de la extremidad inferior están activos durante el ciclo de marcha, especialmente al principio y final de la fase de apoyo y la fase oscilante, debido a aceleraciones y desaceleraciones de la extremidad y transferencias del peso del cuerpo de un pie al otro.…”
Section: Principios Terapéuticosunclassified